Control of Damping off and Increased Growth of Tomato Seeds by Utilizing Trichoderma harzianum Based on Solid Organic Materials - A. Marthin Kalay; Gratiana NC Tuhumury; Novalina Pesireron; Abraham Talaharuruson (Agrologia, 2019)
Low soil fertility and the presence of damping off disease which is a inhibiting factor in the nursery of tomato plants. This can be overcome by utilizing the biological agent Trichoderma harzianum based on solid organic matter (Trichocompost). The aim of the study was to determine the effect of giving Trichocompost and obtain the optimal Trichocompos dose to reduce the intensity of damping off disease and increase the growth of tomato seedlings. The treatments tried were Trichocompos with doses of 20, 40 and 60 tons/ha, designed using a complete randomized design with 10 replications. The plant response observed was the intensity of the disease; height, fresh weight and dry weight of canopy; length, fresh weight and root dry weight. The results showed that the monitoring of Trichocompost can reduce the intensity of damping off disease to 54.80% and increase the growth of tomato seedlings. The recommended Trichocompos dosage is 60 tons/ha or as much as 30 g/1 kg of soil. The results of this study can be used to increase agricultural production and also a solution in an environmentally friendly and sustainable farming system.Keyword: Biocontrol, Tomato Trichocompos, Trichoderma harzianum